The Relationship Between Perceived Social Support and Psychological Well-Being of Women During Menopause - Özdemir, Aysel; Kavak, Funda (T.C. Sağlık Bakanlığı Ankara Şehir Hastanesi, 2021)
Objectives: This research was carried out to determine the relationship between social support perceived by women in the menopause and psychological well-being. Methods: Correlational descriptive type was performed between August 2020 and October 2020. The sample of the study consisted of 500 women registered in 4 FHC s selected from the 10 FHCs connected to Malatya Battalgazi using the draw method. In the research, the sample selection method was not used, data was collected with 300 women who were registered with ASMs and who met the criteria for participation in the research. The Perceived Social Support Scale with Psychological Well-Being was used to collect the data. Results: Perceived social support levels of women participating in the study were determined as 45.77 ± 14.89 (high level) psychological well-being levels as 40.32 ± 10.20 (high level). A statistically significant relationship was found between the perceived social support and psychological well-being scores of women (p

Amaç: Bu araştırma menopoz dönemindeki kadınların algıladıkları sosyal destek ile psikolojik iyi oluş arasındaki ilişkiyi belirlemek amacıyla yapılmıştır. Gereçler ve Yöntem: İlişkisel tanımlayıcı türde Ağustos 2020-Ekim 2020 tarihlerinde arasında yapılmıştır. Araştırmanın örneklemini Malatya Battalgazi’ye bağlı 10 ASM’den kura yöntemi ile seçilen 4 ASM’ye kayıtlı 500 kadın oluşturmuştur. Araştırmada örneklem seçim yöntemine gidilmemiş, ASM’lere kayıtlı olup, araştırmaya katılma kriterlerine uyan 300 kadın ile veriler toplanmıştır. Bulgular: Araştırmaya katılan kadınların algıladıkları sosyal destek düzeyleri 45.77 ± 14.89 (yüksek düzey) psikolojik iyi oluş düzeyleri 40.32 ± 10.20 (yüksek düzey) olarak belirlenmiştir. Kadınların algıladıkları sosyal destek ile psikolojik iyi oluş puan ortalamaları arasında pozitif yönde istatistiksel olarak anlamlı ilişki saptanmıştır (p
MENOPOZ DÖNEMİNDEKİ KADINLARIN PSİKOLOJİK İYİ OLUŞLARI İLE ALGILANAN SOSYAL DESTEK DÜZEYİ ARASINDAKİ İLİŞKİ
Keywords: Obstetrics and Gynaecology; Kadın Hastalıkları ve Doğum